Los insectos escama (Hemiptera: Sternorrhyncha: Coccoidea) presentes en el orquideario de Soroa, Pinar del Rio, Cuba - Mestre, N.=700 1 Ramos, T.; Hamon, A.B.; Evans, G.
(Es, En)
Ilus., 32 ref.
Keywords: ORCHIDACEAE; INSECTA; ESCAMAS; PLANTAS HUESPEDES; CUBA